Long noncoding RNA IGF2AS regulates high‐glucose induced apoptosis in human retinal pigment epithelial cells. Issue 10 (18th July 2019) - Yu, Xiaoyi; Luo, Yingzi; Chen, Gangyi; Liu, Hong; Tian, Ni; Zen, Xiaoting; Liu, Qiuhong
Abstract: High‐glucose‐induced retinal tissue impairment is the major pathological phenotype of diabetic retinopathy. In an in vitro diabetic apoptosis cell model, we evaluated the function of long noncoding RNA, insulin growth factor 2 antisense (IGF2‐AS) in high‐glucose‐injured human retinal pigment epithelial cells. A human retinal pigment epithelial cell line, ARPE‐19 was incubated with high‐glucose in vitro to induce apoptosis. SiRNA‐mediated IGF2‐AS downregulation was conducted in ARPE‐19 cells to evaluate its effect on high‐glucose induced apoptosis, assessed by a TUNEL assay. qRT‐PCR and western blot assays were applied to examine the functional effect of IGF2‐AS on IGF2/AKT/Casp‐9 expressions in glucose‐injured ARPE‐19 cells. ART was further knocked down, specifically in IGF2‐AS‐downregualted ARPE‐19 cells, to investigate its functional involvement in IGF2‐AS‐inhibition‐mediated apoptotic protection in glucose‐injured ARPE‐19 cells. High‐glucose induced apoptosis in ARPE‐19 cells, and upregulated IGF‐2AS in a dose‐dependent manner. SiRNA‐mediated IGF2‐AS downregulation ameliorated apoptosis, upregulated IGF2/AKT and decreased Casp‐9, in high‐glucose‐treated ARPE‐19 cells. AKT knockdown was shown to dramatically reverse the preventive effect of IGF2‐AS‐downregulation on high‐glucose‐induced apoptosis in ARPE‐19 cells. Moreover, it was demonstrated that AKT knockdown directly upregulated Casp‐9 in IGF2‐AS‐downregulated and high‐glucose‐treated ARPE‐19 cells. We demonstrated that inhibiting IGF2‐AS, possibly also through activation of AKT signaling pathway, has a protective function in high‐glucose‐induced apoptosis in human retinal pigment epithelial cells in diabetic retinopathy.